Professionalism and Leadership Competence: A Study of Delta State Ministry of Education - OKEREKA, Onofere Princewill; UTIEYINTSOLA, Gabriel (Management Research and Behavior Journal, 2024)
This study examined the effect of professionalism on leadership competence in Delta State ministry of education, Asaba. The study adopted a cross-sectional research design and to achieve main objective of this study, two hundred and ninety one (291) questionnaires were administered. Out of the 291 copies distributed, 243 were retrieved and analyzed, yielding a response rate of 83.5 percent. The purposive sampling method was employed to specifically select respondents from the Delta State Ministry of Education. This study was anchored on social-learning theory which presupposes that professional need a specialized body of knowledge to be able to promote leadership competence in work setting. Statistical package for Social Sciences (SPSS) version 23 was used to analyze data collected using linear regression analysis. The finding of this study revealed that specialized knowledge, honesty and accountability positively and significantly influenced leadership competence in Delta State ministry of education, Asaba. The study concluded that good management policies, systems and leadership practices can be powerful agents of change. Only a leadership and governance structure with the requisite competency can achieve these goals and advocated for the initiation of a new public sector leadership competence based on professionalism philosophy that calls for responsibilities involving the effective management of people to achieve leadership competence and good performance. This is because specialized knowledge, honesty and accountability are an indispensable requirement for leadership competence and improved performance. The study therefore recommended among others that effective staff specialized knowledge development programs should be a priority of Delta State ministry of education, Asaba while adequate professional support should be given to the staff. This will go a long way to upgrade the skills and competency of the existing staff to make them adaptable to any changing situation